Rapid co-sintering enables ultra-narrow pore size distribution ceria membranes for high-selectivity U(VI)/V(V) separation - Huanyu Zhou; Fan Yu; Minghui Qiu; Xiaowei Da; Xianfu Chen; Kaiyun Fu; Yiqun Fan (Chemical Engineering Journal, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Suppression of Fe loss to promote reconstructed surface via black phosphorus over NiFeB nanosheets for efficient water oxidation - Zehao Wang; Huayu Chen; Yesheng Fu; Hang Yin; Dandan Yu; Junhui Liang; Yuexiang Huang; Liuqi Wang; Wei Gao; Da Chen; Yang Hou (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Binders with cationic semi-interpenetrating networks for sodium-ion batteries under extreme conditions - Chen-Hui Yang; Chi-Hon Leung; Lan-Fang Que; Fu-Da Yu; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Combined failure mechanism of tripod bucket foundations considering torsion effect - Si-Da Wu; Zhuang Jin; Yin-Fu Jin; Zhen-Yu Yin (Ocean Engineering, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Metagenomic perspectives on antibiotic resistance genes in tap water: The environmental characteristic, potential mobility and health threat - Qiyue Meng; Yibo Zhang; Da He; Yu Xia; Jie Fu; Chenyuan Dang (Journal of Environmental Sciences, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Improving ammonia oxidation to nitrogen across wide potential range via synergistic effect over Cu and Ni anchored Metal‐Organic Frameworks - Jiadian Chen; Huayu Chen; Zehao Wang; Yesheng Fu; Dandan Yu; Junhui Liang; Yuexiang Huang; Liuqi Wang; Ismaila Taiwo Bello; Gayi Nyongombe Ekambo; Mokhotjwa Simon Dhlamini; Da Chen (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Experimental investigation of the matching boundary and optimization strategy of a variable geometry turbocharged direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Zhi-fu Zhang; Shi-wei Zhang; Kang-da Wang; Xue-ming Ju; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2024)

Antibiotics ingestion altered the composition of gut microbes and affected the development and reproduction of the fall armyworm - Yan Fu; Luo-Yan Zhang; Qing-Yi Zhao; Da-Ying Fu; Hong Yu; Jin Xu; Song Yang (Journal of Pest Science, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Synthesis of flower-shaped cyclodextrin microporous organic networks for selective recovery of acetophenone and 1-phenylethanol from petrochemical effluents - Yun-Da Yue; Yu Gao; Shi-Ya Fu; Yuan-Yuan Cui; Cheng-Xiong Yang (Chemical Engineering Journal, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Catalytic ozonation for imazapic degradation over kelp-derived biochar: Promotional role of N- and S-based active sites - Da Wang; Shiwen Dong; Siqi Fu; Yi Shen; Tao Zeng; Weiti Yu; Xiaohui Lu; Lizhang Wang; Shuang Song; Jun Ma (Science of The Total Environment, 2023)

Interface engineering of hybrid ZnCo2O4@Ni2.5Mo6S6.7 structures for flexible energy storage and alkaline water splitting - Wen-Duo Yang; Rong-Da Zhao; Fang-Yu Guo; Jun Xiang; Sroeurb Loy; Liang Liu; Jia-Yu Dai; Fu-Fa Wu (Chemical Engineering Journal, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Amplitude modulation of relative humidity by wind in Northeast China: the formation of variance annual cycle in relative humidity - Da Nian; Yu Huang; Zuntao Fu (Climate Dynamics, 2022)

Spatially-explicit quantitative relationship for a potential PES mechanism: Cascade hydropower development in Yarlung Zangbo River Basin, China - Xiao-kang Zhu; Bin Fu; Ramon Felipe Bicudo Da Silva; Ying-man Guo; Chan-yuan Qin; Ting Feng; Hai-bing Yu; Kuang Xiao (Journal of Mountain Science, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Rate Dependence of Splitting Tensile Behaviors of Sandstone and Mudstone - Jun-Jie Wang; Yu-Qiao Li; Fu-Xian Jian; Da Huang (Geotechnical and Geological Engineering, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

In Vivo Biocompatibility and Improved Compression Strength of Reinforced Keratin/Hydroxyapatite Scaffold - Jie Fan; Meng-Yan Yu; Tong-da Lei; Yong-Heng Wang; Fu-Yuan Cao; Xiao Qin; Yong Liu (Tissue Engineering and Regenerative Medicine, 2018)

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Effect of β-glucan on stress tolerances and biocontrol efficacy of Cryptococcus laurentii against Penicillium expansum in pear fruit - Da Fu; Lizhen Zeng; Xiaodong Zheng; Ting Yu (BioControl, 2015)

Spectral Characteristics of Tropical Anvils Obtained by Combining TRMM Precipitation Radar with Visible and Infrared Scanner Data - Yuan-Jian Yang; Da-Ren Lu; Yun-Fei Fu; Feng-Jiao Chen; Yu Wang (Pure and Applied Geophysics, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

SIRT1 interacts with metabolic transcriptional factors in the pancreas of insulin-resistant and calorie-restricted rats - Yong-Ru Chen; Yu-lin Lai; Shao-da Lin; Xi-tao Li; Yu-Cai Fu; Wen-Can Xu (Molecular Biology Reports, 2013)

Quantitative assessment of the effect of ABCA1 gene polymorphism on the risk of Alzheimer’s disease - Xiao-Feng Wang; Yuan-Wu Cao; Zhen-Zhou Feng; Da Fu; Yu-Shui Ma; Feng Zhang; Xiao-Xing Jiang; Yun-Chao Shao (Molecular Biology Reports, 2013)

Effect of dehydroepiandrosterone administration on recovery from mix-type exercise training-induced muscle damage - Yi-Hung Liao; Kun-Fu Liao; Chung-Lan Kao; Chung-Yu Chen; Chih-Yang Huang; Wei-Hsiang Chang; John L. Ivy; Jeffrey R. Bernard; Shin-Da Lee; Chia-Hua Kuo (European Journal of Applied Physiology, 2013)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Amino Acid Homochirality may be Linked to the Origin of Phosphate-Based Life - Da Xiong Han; Hai Yan Wang; Zhi Liang Ji; An Fu Hu; Yu Fen Zhao (Journal of Molecular Evolution, 2010)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)